Analisis Strategi Digital Marketing Fore Coffee dalam Menarik Konsumen Milenial dan Gen Z - Erwin Permana; Nuraini Haliza (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Millennials and Generation Z have made coffee shops a part of their lifestyle. Unlike previous generations, who spent more time at malls. In response to the changing consumer behavior of these different generations, digital marketing strategies have become an effective approach for businesses, including those in the coffee industry. This study aims to analyze Fore Coffee's digital marketing strategies in attracting Millennial and Gen Z consumers. The research was conducted using a descriptive qualitative approach. The research data was sourced from observations of Fore Coffee's digital marketing activities on various social media platforms, as well as in-depth interviews with consumers from the Millennial and Gen Z generations. The results of the study indicate that the digital marketing strategies implemented by Fore Coffee have proven to be an effective approach in attracting attention and building engagement with Millennial and Gen Z consumers. The success of these strategies is supported by the utilization of various digital marketing elements, including the presentation of engaging and interactive content, collaborations with influencers who have credibility in the coffee industry, and the use of video as the primary medium for marketing communication. The Tani Series campaign, which highlights sustainability and the involvement of local coffee farmers, is a concrete example of how Fore Coffee builds a brand image that not only sells products but also has strong social value. Additionally, the collaboration with Mikael Jasin, a professionally recognized barista at the international level, further strengthens Fore Coffee's trust and appeal among young consumers. This study suggests that Fore Coffee should continue to innovate in creating content that is not only engaging but also has strong differentiating value. Furthermore, the dynamic changes in consumption trends and customer preferences demand that Fore Coffee be more responsive in adapting its marketing strategies to remain relevant to the needs and expectations of Millennial and Generation Z consumers.